Pola Komunikasi Komunitas Motor Dalam Membangun Solidariotas Komunitas Girls Ride Karawang - Azizah, Lisna; Oktariani Lubis, Fardiah; Nurkinan (CV. ULIL ALBAB CORP, 2025)
The purpose of this study is to find out how the communication patterns of the Girls Ride Karawang motorcycle community are. To find out the natural communication patterns of the Girls Ride Karawang motorcycle community. This study uses a qualitative research method with a descriptive type because it is to explain and describe the whole thing which is then changed back into written form regarding the description of the role of librarians in improving the quality of repository services. The subject of this study is the communication patterns of the Girls Ride Karawang motorcycle community which is of course located in Karawang City. The data analysis techniques of this study consist of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Girls Ride Karawang Community applies two main communication patterns, namely the star communication pattern and the circle communication pattern. The star communication pattern is characterized by the central role of the chairman as the center of information, decision maker, and solidarity driver. The application of these two patterns simultaneously creates a balance between structure and togetherness, where the management continues to carry out coordinating functions, but members still feel they have space to actively participate in the communication and decision-making process. This finding is in line with Emile Durkheim's thoughts on social solidarity, where communication is the foundation for building a sense of togetherness, mutual trust, and collective responsibility. The solidarity of mechanics in this community is formed from shared values, interests (the automotive world), and shared activities (meetings, touring, social services), and is strengthened by intense and open communication.